Outcomes of a structured education intervention for Latinas concerning breast cancer and mammography. (June 2017) - Laughman, Anna Bawtinhimer; Boselli, Danielle; Love, Magbis; Steuerwald, Nury; Symanowski, James; Blackley, Kris; Wheeler, Mellisa; Arevalo, Gustavo; Carrizosa, Daniel; Raghavan, Derek
Objective: This study examined the utility of living room and church-based small group educational sessions on breast cancer and mammography, for under-served Latinas in North Carolina, USA. Design: Non-randomised, single arm design. Setting: A total of 329 self-selected Latinas participated in 31 small group educational classes in church and home locations in rural and urban settings, and underwent pre- and post-intervention testing of knowledge about breast cancer and mammography. Method: Participants completed educational surveys at baseline before intervention (329), immediately after intervention (329) and 3 months after intervention (223 participants). Results: Misconceptions still exist about breast cancer risk, prevalence and mammography use among Latinas, with the greatest knowledge deficit being in the domain of risk factors. Increases of knowledge were achieved when compared to baseline measures as a result of the interventions described in this paper, which were retained at 3 months re-testing. Many eligible women were not receiving mammograms due to financial barriers. Conclusions: Education sessions of the kind described in this paper are useful in enhancing retained knowledge in breast cancer education for US Latinas.